2020
DOI: 10.3390/ijerph17082833
|View full text |Cite
|
Sign up to set email alerts
|

Meat Safety in Tanzania’s Value Chain: Experiences, Explanations and Expectations in Butcheries and Eateries

Abstract: Urbanisation is associated with changes in consumption patterns and food production processes. These patterns and processes can increase or decrease the risks of outbreaks of foodborne diseases and are generally accompanied by changes in food safety policies and regulations about food handling. This affects consumers, as well as people economically engaged in the food value chain. This study looks at Tanzania’s red meat value chain—which in its totality involves about one third of the population—and focuses on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Regarding the final research question, salience of food safety among vendors, we found that most vendors did not see food safety, cleanliness, or hygiene as a key trait of a successful vendor and that just over half of vendors had any concern about the safety of their food. Similarly low prioritization of food safety, despite documented risks, has been found among meat sellers in Tanzania [ 59 ]. Vendors’ perceptions of food hazards were largely similar to those of consumers, with the exception of cowpea, a product for which vendors acknowledge consumers’ concerns but (at least some) feel that they have adequate technology to mitigate through the use of improved storage bags [ 60 ].…”
Section: Discussionmentioning
confidence: 93%
“…Regarding the final research question, salience of food safety among vendors, we found that most vendors did not see food safety, cleanliness, or hygiene as a key trait of a successful vendor and that just over half of vendors had any concern about the safety of their food. Similarly low prioritization of food safety, despite documented risks, has been found among meat sellers in Tanzania [ 59 ]. Vendors’ perceptions of food hazards were largely similar to those of consumers, with the exception of cowpea, a product for which vendors acknowledge consumers’ concerns but (at least some) feel that they have adequate technology to mitigate through the use of improved storage bags [ 60 ].…”
Section: Discussionmentioning
confidence: 93%
“…For example, the Manyara Region is a dominant source of cattle, with distances to Moshi of several hundreds of kilometers (Allan, 2016). Survey data and interviews (Allan, 2016; Hrynick et al., 2019; Prinsen et al., 2020) indicated beef cattle slaughtered in MMC are on average six years old. The traders collect small numbers of animals, mostly adult males, from livestock keepers or primary markets and deliver them to a terminal market that was considered the “effective origin” for cattle entering the MMC beef supply.…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, postharvest prevalence of NTS is relatively high, certainly in comparison with retail beef products outside Africa (Khen et al., 2014; Thung et al., 2017), so a precautionary approach suggests that strategies for maintaining consumer awareness of the importance of cooking and the risk of cross contamination are appropriate. While awareness of foodborne disease appears high among cooked meat vendors in the study area (Prinsen et al., 2020), we did not address consumer knowledge or household practices. In addition, sensitivity analysis highlighted that transfer coefficients have a strong influence on the model results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Le et al (2020) show that the implementation of good agricultural practices may reinforce confidence and trust amongst downstream stakeholders. In a similar vein, quality upgrading starts with knowledge brokerage on suitable production and postharvest practices (Chengat Maldonado-Siman et al, 2014) but is ultimately dependent on wider cooperation with other food system partners (Le et al, 2020;Prinsen et al, 2020;Supapunt et al, 2021). Little attention is found for socio-economic and environmental outcomes at regional and global levels (Galli et al, 2020).…”
Section: One Segment Of the Papers Focuses On Innovative Cultivation Methods And Farm Management Practicesmentioning
confidence: 99%